Circulating ApoJ is closely associated with insulin resistance in human subjects - Seo, Ji A.; Kang, Min-Cheol; Ciaraldi, Theodore P.; Kim, Sang Soo; Park, Kyong Soo; Choe, Charles; Hwang, Won Min; Lim, Dong Mee; Farr, Olivia; Mantzoros, Christos; Henry, Robert R.; Kim, Young-Bum (Metabolism, clinical and experimental, 2018)
Insulin resistance is a major risk factor for type 2 diabetes. ApolipoproteinJ (ApoJ) has been implicated in altered pathophysiologic states including cardiovascular and Alzheimer's disease. However, the function of ApoJ in regulation of glucose homeostasis remains unclear. This study sought to determine whether serum ApoJ levels are associated with insulin resistance in human subjects and if they change after interventions that improve insulin sensitivity. Serum ApoJ levels and insulin resistance status were assessed in nondiabetic (ND) and type 2 diabetic (T2D) subjects. The impacts of rosiglitazone or metformin therapy on serum ApoJ levels and glucose disposal rate (GDR) during a hyperinsulinemic/euglycemic clamp were evaluated in a separate cohort of T2D subjects. Total ApoJ protein or that associated with the HDL and LDL fractions was measured by immunoblotting or ELISA. Fasting serum ApoJ levels were greatly elevated in T2D subjects (ND vs T2D; 100±8.3 vs. 150.6±8.5AU, P<0.0001). Circulating ApoJ levels strongly correlated with fasting glucose, fasting insulin, HOMA-IR, and BMI. ApoJ levels were significantly and independently associated with HOMA-IR, even after adjustment for age, sex, and BMI. Rosiglitazone treatment in T2D subjects resulted in a reduction in serum ApoJ levels (before vs. after treatment; 100±13.9 vs. 77±15.2AU, P=0.015), whereas metformin had no effect on ApoJ levels. The change in ApoJ levels during treatment was inversely associated with the change in GDR. Interestingly, ApoJ content in the LDL fraction was inversely associated with HOMA-IR. Serum ApoJ levels are closely correlated with the magnitude of insulin resistance regardless of obesity, and decrease along with improvement of insulin resistance in response only to rosiglitazone in type 2 diabetes.